Cytogenetical aspects of testicular cells in economically important species of coreidae family (Heteroptera) - De Souza, Hederson Vinicius [UNESP]; Arakaki, Ricardo Luis Morisugi [UNESP]; Dias, Lidiane Nocente [UNESP]; Murakami, Aline Sumitani [UNESP]; Costa, Luiz Antônio Alves; Bicudo, Hermione Elly Melara de Campos [UNESP]; Itoyama, Mary Massumi [UNESP] (International Society of Cytology, 2007)
Some cytogenetical aspects of spermatozoa formation were studied in 9 Coreidae Brazilian species: Anasa bellator, Athaumastus haematicus, Chariesterus armatus, Dallacoris obscura, Dallacoris pictus, Leptoglossus gonagra, Leptoglossus zonatus, Sphictyrtus fasciatus, and Zicca annulata. Similarly to the other species described to date, all the species studied herein showed cystic spermatogenesis, a reddish membrane covering the testes, a X0 sex determining system, a pair of m-chromosomes, intersticial chiasmata in most autosomes, and autosomes dividing reductionally at first meiotic division and equationally in the second 1 while sex chromosomes, divide equationally and reductionally at first and second meiotic division, respectively. In addition, it was observed that the sex chromosome is heteropycnotic at prophase and that heteropycnotic chromosomal material is found in the nuclei at spermiogenesis. In the species studied, the diploid chromosome number ranged from 19 to 25. It was 19 in S. fasciatus (16A+2m+X0); 21 in A. bellator, A. haematicus, D. obscura, D. pictus, L. gonagra, and L. zonatus (18A+2m+X0); 23 in Z. annulata (20A+2m+X0); and 25 in C. armatus (22A+2m+X0). © 2007 The Japan Mendel Society.
Keywords: Chiasma; Coreidae; Heteroptera; Holocentric; M-chromosome; Meiosis; Anasa; Armatus; Bellator; Chariesterus; Leptoglossus gonagra; Leptoglossus zonatus; Zicca